The clinico-demographic study of morbidity and mortality in patients with organophosphate compound poisoning at tertiary care hospital in rural India - Mundhe, Sanjay A.; Birajdar, Siddheshwar V.; Chavan, Sheshrao S. (International Journal of Advances in Medicine, 2017)
Background: Organophosphates (OP) are commonly used and potentially fatal insecticides. Given the unrestricted availability and widespread use, OP poisoning is very much common following either accidental or intentional exposures. Many parameters are proposed to predict outcome, yet there is no consensus about these parameters. This study aimed to investigate different factors associate with morbidity and mortality in rural population that can help in identifying patients in need of intensive care and treatment to prevent deaths. Methods: This was a cross-sectional observational study of 323 patients, admitted to the tertiary care rural public hospital with OP poisoning between December 2015 to November 2016. Results: Of the 323 patients studied, 62.85% were male, 227 (70.27%) were suicides, 241 (74.61%) ingested OP compounds, 40 (12.38%) patients developed intermediate syndrome and 56 (17.34%) died. There were statistically significant differences between ventilatory support group and no ventilatory group for suicidal intention, sex, comorbid psychiatric conditions, route of exposure, certain clinical features on admission, GCS score, POP scale, time from exposure to initiation of treatment, plasma pseudocholinesterase levels, oxygen saturation, and random blood sugar levels (p<0.05). Conclusions: OP poisoning is a life-threatening condition which requires immediate management. Early initiation of decontamination, atropine and pralidoxime therapy, with supportive ICU care, can save lives. Different demographic, exposure related parameters; some of the clinical features, treatment variables and certain laboratory findings can provide useful prognostic information and help to predict outcomes. A measures to control unchecked availability of these compounds and early transfer of victims to health care facility is needed to save many lives.